Emotion - their meaning and tasks - Gałuszka, Aleksandra (Journal of Education, Health and Sport, 2022)
Emotions are mental states that cause specific physiological changes (e.g. adrenaline secretion), somatic (e.g. change of body posture, facial expression - a "sad" or "scared" expression), cognitive (e.g. thoughts of running away at the sight of a dangerous dog), behavioral (e.g. increased vigilance, running away). The emotional process consists of three basic components:emotional arousal, leading to mobilization changes in the body, the realization of the importance of these changes, the specific and qualitative characteristics of the event of significance for the person. Types of emotional responses: physiological, psychological, behavioral. There are different types of emotions, which are classified in order from the most basic to the emotions learned in different contexts.Therefore, there is a distinction between primary emotions (innate and respond to a stimulus, this includes: anger, sadness, joy, fear, surprise, aversion) and secondary emotions (formed after the primary emotion, shame, guilt, pride, anxiety, jealousy, hope). Positive and negative emotions: affect people's behavior, so some emotions can generate positive actions or reactions, such as joy or satisfaction, but there are other emotions that cause harmful feelings for the individual.